Ultra-wideband terahertz absorber based on metal–graphene hybrid structure. (March 2023) - Liu, Xiao; Chen, Zhihui; Feng, Guang; Song, Jiantong; Liu, Yinshan; Tian, Dongliang; Sun, Fei; Liu, Yichao; Fei, Hongming; Yang, Yibiao
Abstract: In this work, a novel ultra-wideband terahertz absorber composed of the metal metasurface, graphene layer, polyimide substrate and gold reflector is proposed, whose absorption coefficient is over 0.9 from 3.4 THz to 9.1 THz, and absorption bandwidth reaches 5.7 THz (relative bandwidth 91 %). The ultra-wideband absorption is due to the following three factors: the surface plasmon enhanced by metal-graphene hybrid structure, the resonance coupling between hollow cross structure and concentric ring structure on metal metasurface, and the interference cancellation between metasurface and gold substrate. In addition, the absorber is insensitive to polarization angles and incident angles of the incident electromagnetic waves. The research of this paper will provide a new idea for the design of an ultra-wideband absorber, which has potential applications in terahertz imaging, sensors, photodetectors, and modulators. Graphical Abstract: ga1